The Influence Training of BPSDM (Human Resources Education Center Ministry of Transportation) Controling and Work Motivation against Competency of Vocational Teachers in Indonesia - Abadi, Kurniawan; Sutjipto, Sutjipto; Hanafi, Ivan (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to analyze the effect of coaching, supervision and work motivation on the competence of Sailing Vocational Teachers in Indonesia. In addition to knowing whether there is a good relationship between each variable directly. This research uses a quantitative method with a path analysis approach. The population of this study is the Vocational School teachers in Indonesia who have TOT Model Couse 6.09 certificates totaling 362 teachers with a sample of 190 teachers. The results showed the path coefficient of several variables related to teacher competence including coaching, supervision and work motivation. The novelty in this study found that the competence of overseas shipping teachers is dominated by training received in large numbers of 0.418 with the largest indicator which means an increase in knowledge, this is due to being a teacher. Set by IMO (International Maritime Organization)